Chronicle of a Shame: The Role of Civil and Military Authorities During the Arrival of Paramilitary Groups of the United Self-Defense Forces of Colombia (Auc) to Valle Del Cauca (July-August 1999) - González Grisales, Adolfo León (Sociedad y Economía, 2012)
The first military attack of Bloque Calima of the United Self-Defense Forces of Colombia (Autodefensas Unidas de Colombia, AUC) was registered on July 31, 1999, when a group of well-armed men in uniform took the village of La Moralia in mountainous central area of Valle del Cauca killing two inhabitants. This article analyzes the role played by the region’s civil, military and police authorities during the days that preceded and followed this disastrous episode, based on the information published in local and national print media during the months of July and August 1999.